EKSISTENSI AHLI WARIS PENGGANTI DALAM HUKUM ADAT KAMPAR KECAMATAN BANGKINANG PERSPEKTIF KOMPILASI HUKUM ISLAM - Desma Royana; Sofia Hardani; Mohd. Yunus (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2022)
Indigenous Kampar communities, such as those in Bangkinang Sub-district, basically adhere to the principle of matrilineal kinship, therefore each individual draws their lineage FROM the mother's side. The majority of the Kampar indigenous people of Bangkinang sub-district are Muslims. They have the principle of